Evaluation of phytochemical constituents, quantitative analysis and antimicrobial efficacy of potential herbs against selected microbes - Rajeswari A (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objectives: The aim was to evaluate the physicochemical composition, phytochemical analysis and antimicrobial activity of plant extracts. Methods: The plant samples (Citrus reticulata, Camellia sinensis and Punica granatum) were extracted using various solvents (acetone, butanol, chloroform, hexane, methanol and water) and antimicrobial assay was performed against selected microbes viz., Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeuroginosa, Salmonella typhi, Staphylococcus aureus, Aspergillus flavus, Aspergillus niger, Aspergillus parasiticus, Fusarium oxysporum and Fusarium verticilloides. Results: Acetone and aqueous extracts (23 mm) of C. sinensis and P. granatum acquired maximum inhibition. P. granatum found to possess strong antifungal activity in acetone and methanol extract (19 mm) against F. verticilloides. Conclusion: These findings suggest that C. sinensis and P. granatum act as a potential source of the antimicrobial agent. Keywords: Phytonutrients, Plant extracts, Antimicrobial screening, Agar-well dilution, Inhibition.